Aerial dispersal by Actinopus spiderlings (Araneae: Actinopodidae) - Ferretti, Nelson Edgardo (2013)
Ballooning, a form of dispersal rarely seen in mygalomorph spiders, was observed in 13 individuals of an undetermined species of Actinopus under laboratory conditions. After ascending a stick, each spiderling initiated ballooning from either the horizontal lines between sticks or from the stick's edges. They became airborne by dropping and dangling from a dragline, which then gradually lifted and lengthened to 10–15 cm in the breeze, broke at its attachment point, and served as a ballooning thread. This method of ballooning has also been observed in araneomorphs and other species of mygalomorphs, and this is probably a more primitive and shorter distance form of ballooning than that typically practiced by higher araneomorphs, which produce airborne silk lines that are pulled from the spider by air currents and are used either as spanning lines or as balloon lines that allow the spider itself to become airborne.